1992
DOI: 10.1111/j.1365-2362.1992.tb01450.x
|View full text |Cite
|
Sign up to set email alerts
|

Compositional analysis of the collagenous bone matrix. A study on adult normal and osteopenic bone tissue

Abstract: The collagenous constituents of mature bone of 30 individuals 22-93 years of age were studied by post-mortem morphological and biochemical analysis. Morphometric evaluation of the second lumbar vertebral body revealed striking interindividual differences in bone mass, mean trabecular density and mean trabecular thickness. Collagen extracted from vertebral trabecular bone by limited pepsin digestion consisted mainly of collagen I (92%) and collagen V (8%). Immunohistochemistry revealed a distinct distribution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 26 publications
3
24
0
Order By: Relevance
“…To this point, as also suggested by the literature (14)(15)(16)(17), it is worth noting that a changed matrix is certainly relevant to the biological features of bone. Although the main difference between trabecular and cortical bone is the much greater surface area of the former, which explains the differences in bone turnover rates between cortical and trabecular bone, the hypothesis that a modified and possibly defective matrix could somehow be recognized and further removed by osteoclasts cannot be excluded.…”
Section: Discussionmentioning
confidence: 91%
“…To this point, as also suggested by the literature (14)(15)(16)(17), it is worth noting that a changed matrix is certainly relevant to the biological features of bone. Although the main difference between trabecular and cortical bone is the much greater surface area of the former, which explains the differences in bone turnover rates between cortical and trabecular bone, the hypothesis that a modified and possibly defective matrix could somehow be recognized and further removed by osteoclasts cannot be excluded.…”
Section: Discussionmentioning
confidence: 91%
“…16 In addi tion, the expression of collagen phenotype appeared to be modified since type VI collagen amount tended to decrease. 40 An altered level of lysyl hydroxylation of the alpha 2(1) chain of type I collagen in osteoporotic bone has also been demonstrated by Batge et al 41 Notbohm et al have demonstrated that the thermo stability of type I collagen from osteoporotic patients was reduced and was inversely proportional to their degree of lysyl-overhydroxylation, which could in crease type I collagen susceptibility to proteolytic degradation.42…”
Section: Bone Metabolism After Loss Of Normal Biomechanical Functionmentioning
confidence: 94%
“…In human, osteoporotic bones, which exhibit decreased quantity and impaired mineralization of bone, have shown lower content of collagen 18,19) and higher extent of Lys hydroxylation [19][20][21][22] be partly damaged compared to those from fresh bone. However, the contents of collagen (average of 125~128 ìg/mg of dried bone)…”
Section: Discussionmentioning
confidence: 99%